Antifungal Drug Susceptibility of Candida Species Isolated from HIV-Positive Patients Recruited at a Public Hospital in São Luís, Maranhão, Brazil - Terças, Ana L. G.; Marques, Sirlei G.; Moffa, Eduardo B.; Alves, Márcia B.; de Azevedo, Conceição M. P. S.; Siqueira, Walter L.; Monteiro, Cristina A. (Frontiers in Microbiology, 2017)
Abstract Oropharyngeal candidiasis is the most common fungal infection in hospitalized patients with acquired immune deficiency syndrome (AIDS). Its progression results in invasive infections, which are a significant cause of morbidity and mortality. This study aimed to quickly and accurately identify Candida spp. from oral mucosa of AIDS patients recruited at Presidente Vargas Hospital, in São Luís city, Maranhão, Brasil and to evaluate the sensitivity profile of these fungi to antifungals by using an automated system. Isolates were collected from oropharyngeal mucosa of 52 hospitalized AIDS patients, under anti-viral and antifungal therapies. Patients were included in research if they were HIV-positive, above 18 years of age and after obtaining their written consent. CHROMagar®Candida and the automated ViteK-2®system were used to isolate and identify Candida spp, respectively. Antifungal susceptibility testing was performed using the ViteK-2®system, complemented with the E-test®, using the drugs amphotericin B, fluconazole, flucytosine, and voriconazole. Oropharyngeal candidiasis had a high prevalence in these hospitalized AIDS patients (83%), and the most prevalent species was Candida albicans (56%). Antifungal susceptibility test showed that 64.7% of the Candida spp. were susceptible, 11.8% were dose-dependent sensitive, and 23.5% were resistant. All the Candida krusei and Candida famata isolates and two of Candida glabrata were resistant to fluconazole. Most of AIDS patients presented oropharyngeal candidiasis and C. albicans was the most frequently isolated species. The results showed high variability in resistance among isolated species and indicates the need to identify the Candida spp. involved in the infection and the need to test antifungal susceptibility as a guide in drug therapy in patients hospitalized with AIDS. This is the first relate about AIDS patients monitoring in a public hospital in São Luís concerning the precise identification and establishing of antifungal profile of Candida spp.